INNOVATIVE SOUND EFFECTS AND ELEMENTS OF MUSIC NOTATION IN GEORGE CRUMB’S “BLACK ANGELS” FOR ELECTRIC STRING QUARTET - Tudor FERARU (Studia Universitatis Babeş-Bolyai. Musica)
The article discusses the revolutionary compositional ideas and the extremely innovative music notation elements employed by George Crumb in his unique string quartet. The study focuses on the unconventional performance techniques that singularize this particular work. As a musical-theatrical composition, “Black Angels” reflects the spirit of American avant-garde, while at the same time representing an artistic manifest against war and terror. Finally yet importantly, the article attempts to familiarize the reader with a bizarre sound universe, bordering achievements in electronic music, and to promote the work of a highly original author.